Hadith #5088 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abd al-Jlyl bin Atyh عبد الجليل بن عطية القيسي أبو صالح; Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ja'far bin Maymun al-Tamimi جعفر بن ميمون التميمي بياع الأنماط; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
Aban ibn Uthman said: I heard Uthman ibn Affan (his father) say: I heard the Messenger of Allah (ﷺ) say: If anyone says three times: “In the name of Allah, when Whose name is mentioned nothing on Earth or in Heaven can cause harm, and He is the Hearer, the Knower” he will not suffer sudden affliction till the morning, and if anyone says this in the morning, he will not suffer sudden affliction till the evening. Aban was afflicted by some paralysis and when a man who heard the tradition beg
Grade: Sahih